Injured coliforms in drinking water of buildings of Lima Cercado - Vergaray, Germán (2007)
To detect injured coliforms (IC) in drinking water considered suitable for the human consumption according to the Peruvian normativity, were taken and processed 100 water samples of buildings of the district of Lima Cercado. For the analysis the residual free chlorine (RFC) by means of DPD technique and pH was determined using indicating rods Merck. For the count of heterotrophic bacteria (HB) the spread plate method was used, to quantify total Coliform (TC) and fecal Coliform (FC) the techniques of multiple tubes and membrane fi lter were used. In order to recover and to enumerate injured TC and FC the m-T7 medium were used. For the bacterial specifi cation the standard tests and API 20E system. For CI’s detection there were in used the samples that turned out to be negative for TC and FC and/or had count of HB an equal or lower to 500 UFC/mL. Using the conventional methods was demonstrated that 15% of the water samples was insuitable for the human consumption. Of the considered suitable 85, 29,41% (25) was containing IC. In the suitable samples using the conventional methods, 60% (9) had between 0.1 and 0.5 ppm of RFC and in the considered insuitable samples for having IC, 88% (22) had between 0.1 and 1.0 ppm. Relation was not demonstrated between pH and unsuitable samples. Among the IC were identifi ed: Escherichia coli, Enterobacter aerogenes, E. cloacae, Enterobacter sp, Citrobacter freundii, Citrobacter spp and Klebsiella sp. The drinking water considered suitable by the Peruvian normativity can be contaminated by intestinal microorganisms and constitute a risk for the health; the residual free chlorine between 0.1 and 1.0 ppm does not guarantee the elimination of the intestinal bacteria.